2017
DOI: 10.1101/226308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

UV-Induced Keratin 1 Proteolysis Mediates UV-Induced Skin Damage

Abstract: Keratins play critical roles in intermediate filament formation, inflammatory responses and cellular signaling in epithelium. While keratins is a major epidermal fluorophore, the mechanisms underlying the autofluorescence (AF) of keratins and its biomedical implications have remained unknown. Our study used mouse skin as a model to study these topics,showing that UV dose-dependently induced increases in green AF at the spinous layer of the epidermis of mouse within 6 hr of the UV exposures, which may be used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Since the structure of the LPS-induced green AF is similar with the UV-induced green AF (13), which exhibits the characteristic polyhedral structure of the keratinocytes in Stratum Spinosum, the LPS-induced green AF could also be located in the keratinocytes in Stratum Spinosum. Because the only epidermal fluorophores 1 2 that selectively exist in the keratinocytes of Stratum Spinosum are keratin 1 and keratin 10 (8,20,26), our study has suggested that keratin 1 and/or keratin 10 are the origin of the LPS-induced increases in the epidermal green AF.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Since the structure of the LPS-induced green AF is similar with the UV-induced green AF (13), which exhibits the characteristic polyhedral structure of the keratinocytes in Stratum Spinosum, the LPS-induced green AF could also be located in the keratinocytes in Stratum Spinosum. Because the only epidermal fluorophores 1 2 that selectively exist in the keratinocytes of Stratum Spinosum are keratin 1 and keratin 10 (8,20,26), our study has suggested that keratin 1 and/or keratin 10 are the origin of the LPS-induced increases in the epidermal green AF.…”
Section: Discussionmentioning
confidence: 94%
“…As described previously (13), the epidermal AF of the ears of the mice was imaged under a two-photon fluorescence microscope (A1 plus, Nikon Instech Co., Ltd., Tokyo, Japan), with the excitation wavelength of 488 nm and the emission wavelength of 500 -530 nm. The AF was quantified as follows: Sixteen spots with the size of approximately 100 X 100 μm 2 on the scanned images were selected randomly.…”
Section: Imaging Of Epidermal Afmentioning
confidence: 99%
“…3) Compared with Low-Risk persons -the persons with relatively mild cardiovascular diseases such as hypertension, severe cardiovascular diseases and cerebrovascular diseases such as AIS can produce significant increases in the AF intensity (3). 4) We have found that keratin 1 -a major cytoskeletal protein -is rapidly degraded by such oxidative stress generators as UV (12,13). Therefore, our green AF-based evaluation method is not merely a method of 'risk evaluation'.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have indicated that the increased epidermal green AF indicates the injury levels produced by oxidative stress or inflammation, instead merely a probability of injury: 1) We have found that in healthy persons (3) and normal mice that are not exposed to UV (12,13) or inflammation-inducing agents (26), the basal epidermal green AF is at very low levels. 2) Such insults as UV (12,13) and LPS (26) can dose-dependently increase the epidermal AF intensity. 3) Compared with Low-Risk persons -the persons with relatively mild cardiovascular diseases such as hypertension, severe cardiovascular diseases and cerebrovascular diseases such as AIS can produce significant increases in the AF intensity (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation